Pengaruh Magnitude Moment Terhadap Potensi Likuefaksi Tanah Loose Sand Jenuh Air Menggunakan Model UBC3D-PLM - Yuki Achmad Yakin; Desti Santi Pratiwi; Farhan Tri Jaelani (Fakultas Teknik, 2023)
Liquefaction is a decrease in the shear strength of the soil caused by an increase in pore water pressure until it is equal to the strength value of the soil. The Plaxis 2D application with the UBC3D-PLM model is used in this study to analyze the effect of the magnitude moment on soils with liquefaction potential, the effect of the magnitude moment on the increase in pore water pressure ratio, the effect of different soil densities, and the effect of the depth of loose soil on the potential for liquefaction. The effect of moment magnitude on liquefaction potential is obtained from the results of data modeling analysis. The analysis results show that the potential for liquefaction increases with the magnitude of the moment. On the other hand, the liquefaction probability is lower when the moment magnitude is smaller. This study shows that an earthquake with a magnitude of 6.95 (Mw) occurs in loose and medium-dense soils. Meanwhile, an earthquake with a moment magnitude of 5.5 (Mw) only occurs on soils with loose density. Meanwhile, the earthquake with a moment magnitude of 4.27 (Mw) did not experience liquefaction at any soil density.